2010
DOI: 10.3758/app.72.6.1601
|View full text |Cite
|
Sign up to set email alerts
|

Language identification from visual-only speech signals

Abstract: Our goal in the present study was to examine how observers identify English and Spanish from visual-only displays of speech. First, we replicated the recent findings of Soto-Faraco et al. (2007) with Spanish and English bilingual and monolingual observers using different languages and a different experimental paradigm (identification). We found that prior linguistic experience affected response bias but not sensitivity (Experiment 1). In two additional experiments, we investigated the visual cues that observer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Another feature of language is rhythm. [41] explains that babies have the ability to distinguish languages based on acoustic rhythm, and [42] suggests that adults also have this ability and furthermore, rhythm is expressed visually. Further work into VLID could therefore focus on incorporating both of these additional language cues and evaluating their contribution to language discrimination.…”
Section: Overall Conclusion and Future Workmentioning
confidence: 99%
“…Another feature of language is rhythm. [41] explains that babies have the ability to distinguish languages based on acoustic rhythm, and [42] suggests that adults also have this ability and furthermore, rhythm is expressed visually. Further work into VLID could therefore focus on incorporating both of these additional language cues and evaluating their contribution to language discrimination.…”
Section: Overall Conclusion and Future Workmentioning
confidence: 99%
“…Specifically, Ronquest et al [21] carry out experiments in which participants are asked to observe, without listening, video clips that show a male or a female speaker talking in English or Spanish. Both speakers appearing in the videos are bilingual in English and Spanish.…”
Section: B Visual Speech and Accentmentioning
confidence: 99%
“…However, the beneficial role of visual information to speech comprehension has been well documented [17] and experimentally validated [18]- [20]. Furthermore, recent findings indicate that human observers can actually perform language identification through the visual modality only [21]. Automated approaches for visual-only language identification have also been proposed (e.g., [22]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been found that both bilingual and monolingual Spanish and Catalan speakers, but not speakers of English and Italian, can discriminate Catalan and Spanish using only visual cues (Soto-Faraco et al, 2007). Also both monolingual and bilingual English- and Spanish-speaking adults have been shown to discriminate between Spanish and English only on the basis visual cues (Ronquest et al, 2010). Likewise, Navarra et al (2014) showed that English and Spanish/Catalan adult speakers do exploit visual information concerning the temporal distribution of consonant and vowel intervals to discriminate languages that differ in this speech property such as English and Japanese.…”
Section: Discussionmentioning
confidence: 99%
“…For example, bilingual Spanish-Catalan as well as monolingual Spanish and Catalan speakers, but not monolingual speakers of English and Italian, can discriminate Catalan and Spanish using only visual cues (Soto-Faraco et al, 2007). Also monolingual and bilingual English- and Spanish-speaking adults have been shown to discriminate between Spanish and English—two languages differing at the basic rhythmic level—only on the basis of the visual cues provided by speaking faces (Ronquest et al, 2010). These results suggest that adult listeners can discriminate between rhythmically similar (Spanish and Catalan) as well as rhythmically different (English and Spanish) languages by analyzing the facial mimic when they know at least one of the two languages.…”
Section: Introductionmentioning
confidence: 99%